Sebuah Pendekatan Baru Pengembangan Aplikasi Web Cerdas Untuk Memonitor dan Menganalisa Gangguan Kualitas Daya Listrik Kampus Uin Suska Riau Menggunakan Asynchronouse JavaScript XML, S-Transform dan Support Vector Machine - Fitri Amillia (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Now days, power quality problems are important issues; this is caused using electronic devices is increasingly widespread as information technology equipment, programmable logic controllers, adjustable speed drives, computers, industrial machinery, energy-saving lamps resulted in a change in the nature of the electrical load. The burdens of non-linear cause disturbance to the voltage waveform can result in poor quality of power. This study proposes a new approach in developing intelligent web application to monitor and analyze power quality disturbances using web programming techniques namely Asynchronous Java Script XML, S-transform technique as feature extraction and Support Vector Machine (SVM) as classifier. The test results using K-fold cross validation technique showed that the average accuracy of the system to identified power quality disturbances is 99.34%. This proves that this method is best used to identify power quality disturbances on the web; it can be access anywhere and at anytime. Keywords:Electrical power quality, Asynchronous Java Script XML,S -transform, Support Vector Machine